Use of catecholamines and corticosteroids in alpha adrenergic hypovolemic and septic shock blockers. - Pereda Castillo, Santiago (2015)
Shock one fault in the central pressure is a defect in tissue perfusion. In hemorrhagic or hypovolemic and septic shock this defect is due to a decrease in cardiac output, rather than to a drop in peripheral vascular resistance; this is generally increased.